Fabrication and optimization of physicochemical properties of nano-phytosome from Punica granatum L. peel enriched polyphenol extract - Davoud Kazemi; Samad Nejad Ebrahimi; Reza Mohsenian Kouchaksaraee (Institue of Medicinal Plants, ACECR, 2022)
Background: Punica granatum L. peel is a rich source of phenolic compounds such as punicalagin and ellagic acid that represent a major part of the fruit and many fruit by-products in Asian countries, mainly Iran. Objective: The purpose of this study is to design a value-added pomegranate peel product. Methods: For this purpose, a safe and environmentally friendly method of resin column chromatography was used to enrich the hydroalcoholic extract of pomegranate peel with punicalagin. The enrichment conditions were optimized in terms of column condition and the amount of extract used. The results were monitored and confirmed by HPLC-PDA. In order to improve the physicochemical properties of the enriched extract, the obtained extract was loaded onto nano-phytosome by thin-film hydration method. FT-IR confirmed the nano-phytosome structure. Results: The resin column was optimized at a 3:1 resin-to-extract ratio in an optimum contact time duration of 30 minutes (80.50 %) and a 2.63-fold increase in the phenolic compounds compared to the crude extract. The results indicated that encapsulation efficiency was equal to 58 %, the particle size was equal to 154.0 to 216.5 nm, and one-year stability was achieved with an optimal polydispersity index of 0.215-0.287 in terms of particle size. Conclusion: The enrichment of the crude extract before formulation and fabrication polyphenol enriched extract is a promising strategy to transform of pomegranate peel into a valuable product.